Fenton-like application to pretreated cheese whey wastewater - Prazeres, Ana (2013)
Cheese whey wastewater has been treated by the Fenton-like oxidation system after being pre-processed through a coagulation – flocculation stage with FeCl3 or alternatively, through a sedimentation step with Ca(OH)2 plus aerobic digestion. In the first case, Fenton-like oxidation is capable of reducing the initial COD (chemical oxygen demand) to 80% of the initial value, 20% of COD shows recalcitrance to chemical oxidation regardless of the operating conditions used. In the second case, the oxidation system is capable of removing almost the total COD present in the pretreated effluent. Given the lower values of initial COD, complete COD conversion is achieved at short reaction times within minutes depending on the initial reagent concentration. Removal of Fe(III) from the oxidation treatment can be achieved by Ca(OH)2 addition. Sedimentation pH significantly affects the observed settling rate. Hence, neutral conditions lead to better results than slightly acidic pHs.